Does Farm Size Matter for Food Security Among Agricultural Households? Analysis of Indonesia’s Agricultural Integrated Survey Results - Kadir Ruslan; Octavia Rizky Prasetyo (Proceedings of The International Conference on Data Science and Official Statistics, 2023)
Most agricultural households in Indonesia are small-scale farmers making them prone to food insecurity. Until recently, no study has assessed the impact of farm size and sociodemographic characteristics on the food insecurity status of agricultural households using a nationwide agricultural household survey in Indonesia. Our study aims to address this gap by utilizing the results of the first Indonesian Agricultural Integrated Survey conducted by BPS in 2021. Applying the Rasch Model, Multinomial Logistic Regression, and Ordinary Least Squares Regression, we found that the farm size has a positive impact in lowering the likelihood of experiencing moderate or severe levels of food insecurity among agricultural households. Our study also found that agricultural households with a higher probability of being food insecure are characterized by having higher members of households, relying only on agricultural activities for their livelihood, lower education attainment of household heads, and being led by female farmers.